Ferritic stainless steel plate with excellent anti-ridging properties
By incorporating Ce oxides as inclusions and optimizing the equiaxial crystal ratio in ferritic stainless steel sheets, the issue of rising during molding is effectively addressed, resulting in improved surface quality and processability.
Patent Information
- Application Number
- JP2021053151
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Ferritic stainless steel sheets often exhibit rising, a waving-like uneven pattern, during molding, which degrades their aesthetic appearance and can lead to local thickness deviations and cracks.
A ferritic stainless steel sheet composition with Ce oxides as inclusions and a high equiaxial crystal ratio, where the Ce content and total oxygen concentration are controlled within specific ranges to produce Ce oxide-based inclusions that act as solidification nucleation sites, thereby reducing rising during molding.
The controlled composition and inclusion distribution result in a ferritic stainless steel sheet with excellent rising resistance, minimizing uneven surfaces and thickness deviations, and enhancing the sheet's processability and surface quality.
Smart Images

Figure 0007654440000003 
Figure 0007654440000001 
Figure 0007654440000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel sheet having excellent ridging resistance. [Background technology]
[0002] Currently, many types of stainless steel sheets are used in a wide range of applications. One type of stainless steel sheet, austenitic stainless steel sheet, is used as a structural material for industrial and domestic use because it has excellent corrosion resistance, workability, and surface properties. In contrast, ferritic stainless steel sheets contain almost no Ni compared to austenitic stainless steel sheets, making them inexpensive, and because they have a small thermal expansion coefficient, they have come to be widely used in fields such as roofing materials for large facilities, various kitchen appliances, and automobile exhaust system components. However, when ferritic stainless steel sheets are subjected to forming processes such as pressing and rolling, a wavy uneven pattern called ridging (hereinafter simply referred to as "ridging") that runs along the forming direction can occur on the steel sheet surface. When ridging occurs on the surface of a steel sheet, it mars the appearance of the steel sheet surface, so the steel sheet surface is polished to remove the ridging during production. However, during the production process, ridging leads to localized thickness deviations, which can lead to the problem of cracks occurring depending on the processing method.
[0003] It is believed that this ridging occurs because columnar crystals grow in the same direction in the solidification structure, and a colony of an aggregate structure with the same crystal orientation is formed by rolling and annealing. Based on this knowledge, there have been various researches and reports on improving ridging (for example, Non-Patent Document 1). For ferritic stainless steel sheets to be used in more diverse fields, it is desired that the formed products after processing do not have ridging or cracks. Meanwhile, ridging, which is likely to occur when ferritic stainless steel sheets are press-formed, is caused by the fact that the coarse columnar crystal structure generated during continuous casting is not sufficiently destroyed in the hot rolling process and the cold rolling process, forming a colony that is a collection of multiple crystal grains with similar crystal orientations. In response to this, it is known that the occurrence of ridging can be suppressed by forming a ferritic stainless steel sheet into a metal structure in which a large number of equiaxed crystals with random crystal orientations are generated.
[0004] For example, Patent Document 1 proposes a method of improving ridging resistance by using REM oxides. Specifically, the composition of inclusions in steel for improving ridging resistance is such that the concentration range of each oxide in a composite inclusion composed of REM oxides, Al2O3, SiO2, MnO, and Cr2O3 is limited to homogenize the recrystallized structure during rolling and annealing, thereby improving ridging resistance. However, Patent Document 1 presents a composite oxide of REM oxides and Al2O3, and although each component of REM has a stronger affinity for oxygen than Al, it is said that a composite oxide containing Al2O3 is formed, and the specific action and effect of the specific oxide form for each component of REM is unknown, which is problematic in that the effect is insufficient. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4238454 [Non-patent literature]
[0006] [Non-Patent Document 1] Shozo Mizoguchi: 177th and 178th Nishiyama Memorial Technical Lectures (2001), 53 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in view of the above problems, and an object of the present invention is to provide a ferritic stainless steel sheet having excellent ridging resistance and reduced occurrence of ridging due to forming, by having inclusions which are oxides of Ce in REM (hereinafter referred to as Ce oxides) and thereby increasing the amount of equiaxed crystals in the metal structure. [Means for solving the problem]
[0008] In order to solve the above problems, the gist of the present invention is as follows. (1) In mass%, C: 0.001-0.03%, Si: 0.2-1.0%, Mn: 0.05-1.0%, P: 0.001-0.04%, S: 0.001-0.01%, Cr: 10.5-31.0%, Al: 0.006-0.20%, Nb: 0.03-0.8%, Ti: 0.01-0.2%, N: 0.001-0.03%, Ce: 0.01-0.35%, and TO (total oxygen concentration): 0.001-0.01%. The steel sheet has a composition in which the product of the Ce content (%) and the TO content (%) satisfies the inequality relationship of the following formula (1), and has a steel structure in which Ce oxide-based inclusions formed by the combination of Ce and oxygen (O) are present, and among the Ce oxide-based inclusions, those having a circle equivalent diameter of 1 to 5 μm are within 1 cm within a cross section perpendicular to the rolling direction of the steel sheet. 2 The density of each particle is 20 particles / cm 2 The above-mentioned ferritic stainless steel sheet has excellent ridging resistance. Formula (1): 1.0×10 -5 ≦(Ce(%))×((TO(%))≦1.5×10 -3 (2) A ferritic stainless steel sheet having excellent ridging resistance according to claim 1, containing, by mass%, one or more components selected from the group consisting of Cu: 0.01 to 2.0%, Mo: 0.01 to 3.0%, W: 0.002 to 3.0%, La: 0.001 to 0.05%, and Y: 0.001 to 0.008%. Effect of the Invention
[0009] In the present invention, by controlling the amounts of Ce and TO (total oxygen concentration) within appropriate ranges and by controlling the number density of Ce oxide-based inclusions in a ferritic stainless steel sheet, it is possible to obtain a metal structure with a large number of equiaxed crystals, and to obtain a ferritic stainless steel sheet with excellent ridging resistance and little occurrence of ridging during forming. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph showing the relationship between the number density (number / cm2) of Ce oxide-based inclusions having an equivalent circle diameter of 1 to 5 μm and the ridging height (μm). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Specific embodiments of the present invention will be described below. Note that the present invention is not limited to the following embodiments, and various modifications are possible without departing from the spirit and scope of the present invention.
[0012] (Ferritic stainless steel plate) The ferritic stainless steel sheet of the present invention has, by mass%, C: 0.001-0.03%, Si: 0.2-1.0%, Mn: 0.05-1.0%, P: 0.001-0.04%, S: 0.001-0.01%, Cr: 10.5-31.0%, Al: 0.006-0.20%, Nb: 0.03-0.8%, Ti: 0.01-0.2%, N: 0.001-0.03%, Ce: 0.01-0.35%, and TO (total oxygen concentration): 0. The steel sheet has a composition in which the product of the Ce content and the TO content satisfies the inequality relationship of the following formula (1), and has a steel structure in which Ce oxide-based inclusions formed by the combination of Ce and oxygen (O) are present, and among the Ce oxide-based inclusions, those having a circle equivalent diameter of 1 to 5 μm are within 1 cm within a cross section perpendicular to the rolling direction of the steel sheet. 2 The density of each particle is 20 particles / cm 2 The ferritic stainless steel sheet of the present invention will now be described in detail. The reasons for limiting the composition of the present invention will now be described.
[0013] (Production of solidified tissue) In order to obtain a ferritic stainless steel sheet (hereinafter simply referred to as "steel sheet") with excellent ridging resistance, comparative experiments were conducted using the following method to clarify the effects of each oxide formed by rare earth metals (hereinafter sometimes referred to as "REM") such as Ce (cerium), La (lanthanum), and Y (yttrium). First, the raw materials were put into a 100 kg vacuum melting furnace and melted. The refractory material used in the furnace was dolomite-based refractory material used in actual operation. Melting was performed under a vacuum atmosphere, and after melting, the molten steel temperature was kept at 1600°C. After holding for 20 minutes, deoxidization and desulfurization were performed. Aluminum (Al) was used as the deoxidizing and desulfurizing agent, and after Al deoxidization, Ce, La, Y, and other components were added in different amounts. Each sample in the molten state was poured into a mold and solidified after adjusting the superheat degree to about 30 to 50°C relative to the liquidus temperature. The obtained ingot was cut at a specified position. The cut surface was then etched to reveal the solidified structure.
[0014] (Relationship between Ce and TO) The solidification structure of each ingot containing either Ce, La, or Y was observed. As a result, in the ingot to which Ce was added, when the Ce concentration was 0.01 to 0.35% and the TO (total oxygen concentration) was 0.001 to 0.01%, and formula (1) was satisfied, the solidification structure was a fine solidification structure with many small crystal grains, without the development of large columnar crystals. Formula (1): 1.0×10 -5 ≦(Ce(%))×((TO(%))≦1.5×10 -3
[0015] (Equiaxed crystal) It forms a solidification structure from molten steel to ingot, and increases the equiaxed crystal ratio in the solidified state. Specifically, by adding an appropriate amount of Ce in REM to molten steel before casting, Ce and oxygen (O) combine to generate Ce oxide-based inclusions (hereinafter referred to as "Ce oxide-based inclusions") in the molten steel, and these Ce oxide-based inclusions become solidification nucleation sites, generating a large number of fine equiaxed crystal grains during solidification. By subjecting this ingot to hot rolling, cold rolling, annealing, and other processes, a steel plate with a high equiaxed crystal ratio can be obtained. In formula (1), when Ce (%) and TO (%) are low, there are few solidification nucleation sites during solidification, and the equiaxed crystal ratio cannot be increased, and columnar crystals are increased, and the equiaxed crystal ratio cannot be increased even when the steel plate is made. In formula (1), when Ce (%) is high and TO (%) is low, there are few Ce oxide-based inclusions in the molten steel that are generated, and they do not act as solidification nucleation sites. In addition, when the Ce (%) is low and the TO (%) is high in formula (1), the amount of Ce oxide-based inclusions in the molten steel is small, and the equiaxed crystal ratio cannot be increased. Therefore, it is clear that formula (1) must be satisfied in order to increase the equiaxed crystal ratio in the ingot and when it is made into steel plate.
[0016] (Evaluation of equiaxed crystal ratio) This refined solidification structure with many small crystal grains was evaluated as the equiaxed crystal fraction using formula (2). As shown in formula (2), the equiaxed crystal fraction represents the area ratio (%) of equiaxed crystal grains to the entire surface of the ingot. Formula (2): Equiaxed crystal ratio (%) = area of equiaxed crystal structure ÷ (area of entire ingot surface) × 100 In the solidification structure of the molten ferritic stainless steel of the present invention, the equiaxed crystal ratio was a high value of 80 to 98%. However, when other rare earth metals, such as La, Y, Sc, and Nd, contained in REM other than Ce, were added, the effect of increasing the equiaxed crystal ratio of the solidified structure and refining the grain size could not be obtained even if the amount of addition was changed.
[0017] (Evaluation of Ce oxide inclusions) In addition, a 50 mm thick block for hot rolling was cut out from the ingot with each Ce concentration. After heating each block at 1180 to 1200 °C for about 30 minutes, a 4 mm thick hot rolled sheet was obtained. The hot rolled sheet was then annealed, the surface oxide scale was removed, and cold rolling was performed to obtain a 0.8 mm thick cold rolled steel sheet. The cold rolled steel sheet was then finish annealed at 1000 °C, and the oxide scale was removed by pickling. JIS-5 test pieces, as specified in JIS Z2214 (Metal Material Tensile Test Method), were taken from the obtained cold rolled steel sheet parallel to the rolling direction. After 15% tension with a tensile tester, the occurrence of ridging on the sheet surface was investigated. In addition, a sample for inclusion investigation was cut out from the steel sheet, and the size and number per unit area of Ce oxide-based inclusions inside the sheet were investigated.
[0018] (Measurement of circle equivalent diameter and number density of Ce oxide inclusions) A specific method for investigating Ce oxide-based inclusions was to cut multiple sheets perpendicular to the rolling direction of the cold-rolled steel sheet (hereinafter, the cut surface will be referred to as "C cross section"), and to use an MQA (Metal Quality Analyzer (registered trademark)) device to analyze the C cross sections. The size of the Ce oxide-based inclusions on the C cross sections in the width direction of the cold-rolled sheet is almost the same as the width of the Ce oxide-based inclusions before rolling. The inclusion composition was investigated using an MQA composition analyzer. Furthermore, the size of the Ce oxide-based inclusions was calculated as a circle equivalent diameter based on the area measured with the MQA. The circle equivalent diameter of Ce oxide-based inclusions is the diameter of a perfect circle equivalent to the area of the target. The number of Ce oxide-based inclusions per unit area was calculated based on the number of Ce oxide-based inclusions per unit area per cm in a cross section perpendicular to the rolling direction of the steel sheet. 2 The number of inclusions per square centimeter was calculated based on the number of inclusions counted as Ce oxide-based inclusions by measuring the composition of the inclusions with MQA. 2 ) was calculated.
[0019] (Relationship between number density of Ce oxide inclusions and ridging height) The inclusions found inside the steel sheet were Ce oxide-based inclusions, and the number of Ce oxide-based inclusions with a circle equivalent diameter of 1 to 5 μm was measured. Furthermore, the number density (pieces / cm) of Ce oxide-based inclusions with a circle equivalent diameter of 1 to 5 μm was measured inside the steel sheet of the present invention. 2 ) is 20 (pieces / cm 2 The correlation between the number of recrystallization gaps observed inside the steel sheets and the number density of Ce-oxide inclusions per unit area of steel sheets with each Ce concentration was investigated. The results of the investigation are shown in Figure 1.
[0020] (Evaluation of Ridging Resistance) Figure 1 shows the number density (number / cm) of Ce oxide inclusions with a circle equivalent diameter of 1 to 5 μm. 2 ) and ridging height (μm). Ridging resistance was evaluated according to the waviness height on the steel sheet surface. The greater the waviness height on the steel sheet surface, the lower the ridging resistance. Ridging resistance was evaluated on a five-level scale, with ridging height (μm) of 5 μm or less being A rank, over 5 μm and 10 μm or less being B rank, over 10 μm and 15 μm or less being C rank, over 15 μm and 20 μm or less being D rank, and over 20 μm being E rank. Among these, if the ridging height is 10 μm or less and the ridging runk is either A or B rank, the steel sheet is judged visually to be almost imperceptible of unevenness, and therefore it can be said that the ridging resistance is problematic in practical use. On the other hand, if the ridging height is 10 μm or more and the ridging runk is either C to E rank, the steel sheet is judged visually to be clearly observable as ridging in the form of waviness or unevenness, and therefore it can be said that the ridging resistance is problematic in practical use. Therefore, from Fig. 1, the number density (pieces / cm) of Ce oxide inclusions with a circle equivalent diameter of 1 to 5 μm 2 ) is 20 (pieces / cm 2 ) From the above, it can be seen that the ridging resistance of steel sheets with ridging ranks of A and B is within the practical range.
[0021] (Suppression of ridging) It is generally believed that the occurrence of ridging is due to the fact that the coarse columnar crystal structure formed during continuous casting is not sufficiently destroyed during the hot rolling process, and yet the texture of the coarse columnar crystals remains. This texture can also cause cracks and anisotropy during processing, resulting in reduced workability. To suppress this texture, it is effective to repeat cold rolling and annealing multiple times after hot rolling to refine the metal texture through recrystallization. However, repeating cold rolling and annealing multiple times places a burden on the process, leading to increased manufacturing costs and reduced productivity, and is not suitable for mass production of inexpensive steel sheets. In addition, it is not necessarily easy to completely eliminate the effects of the texture using such a method. Ce oxide inclusions have a high melting point, are not easily softened, and are hard, so they are not destroyed or refined as Ce oxide inclusions even during hot rolling and cold rolling, and even when heat is applied by annealing, they act effectively as sites that hinder the growth of crystal grains. Therefore, the Ce oxide inclusions can suppress the growth of crystal grains during forming, and can suppress the occurrence of ridging during forming.
[0022] As can be seen from Figure 1, the more the number of Ce oxide inclusions increases, the more the rib runk improves. The reason for this improvement in the rib runk was examined from the perspective of the mechanism of refining the solidification structure. In the case of ordinary steel, the idea of generating many heterogeneous nuclei to serve as nucleation sites during solidification has been reported (Academic literature: BLB Ramfitt: Metall. Trans., 1 (1970), 1987.)
[0023] (Particle size of Ce oxide inclusions) Furthermore, the Ce oxide inclusions should have an equivalent circle diameter in the range of 1 to 5 μm. It was found that the solidification structure becomes fine when a necessary number of inclusions with an equivalent circle diameter of 1 to 5 μm are present. However, if the diameter exceeds 5 μm, the number of collisions between the inclusions increases, causing them to aggregate and coalesce into clusters. In this case, they do not become solidification nucleation sites, but rather become the cause of defects in the steel sheet. From the above results of the investigation, it is necessary to consider the particle size of the Ce oxide inclusions in relation to the equivalent circle diameter and number density, including their function as sites.
[0024] (Components of Ce oxide inclusions) In the present invention, other rare earth metals such as La, Y, Sc, and Nd contained in REM other than Ce have almost no effect on ridging. Ce oxide inclusions are compounds of cerium and oxygen, and have various forms such as CeO2 and Ce2O3, and may be formed alone or in combination. Ce oxide inclusions may also contain oxides of La, Y, Sc, Nd, etc.
[0025] (Effect of Ce on Ferritic Stainless Steel Sheets) The ferritic stainless steel sheet of the present invention is different from ordinary steel in that it contains 10.5 to 31.0% Cr, but the C and N concentrations are low, so it is in the ferrite phase from the start of solidification to room temperature. However, since it contains a large amount of Cr, the value is different from the lattice constant of ordinary steel. Therefore, the crystal mismatch between the lattice constant of the primary crystal formed during solidification and the Ce oxide-based inclusions was predicted by temperature correction. As a result of the calculation, the crystal mismatch was 6 to 9%. In other words, it is presumed that the difference between the crystal lattice spacing of the ferrite phase and the crystal lattice spacing of the Ce oxide-based inclusions is small, and the Ce oxide-based inclusions are in a state where they are likely to become solidification nucleation sites of the ferrite phase, and as a result, the equiaxed crystal ratio is high. When other REMs were added, the effect of refining the solidification structure was not obtained even if the amount of addition was changed. It is presumed that this is because the difference in the crystal lattice spacing between La oxide, Al oxide, etc. and the ferrite phase is large.
[0026] (composition) Each component of the present invention will be described below. Note that the unit of the content of each element in the stainless steel sheet is "mass %", but hereinafter, unless otherwise specified, it will be simply indicated as "%". (C:0.001~0.03%, N:0.001~0.03%) Both C (carbon) and N (nitrogen) are elements that affect corrosion resistance and mechanical properties. In particular, when their respective contents exceed 0.03%, their adverse effects become more pronounced, so the lower the C and N concentrations, the better the corrosion resistance and other properties will be. However, removing C and N places a large refining burden on molten stainless steel, and reducing the C and N contents to C<0.001% and N<0.001% is industrially uneconomical.
[0027] (Si: 0.2-1.0%) Silicon (Si) is an effective element as a deoxidizer. If the concentration of Si is lower than 0.2%, its effect as a deoxidizer decreases. Furthermore, if Ce is added after adding Si, the already formed MnO and Cr2O3 may chemically react with Ce oxide inclusions to form composite oxides. This composite oxide does not function effectively as a nucleation site because it does not have good crystal matching with primary ferrite. When excessive Si is added, the generated SiO2 reacts with Ce oxide inclusions to generate composite oxides. In this case, too, it does not function as a nucleation site as described above. Therefore, the amount of Si added is set to 0.2 to 1.0%.
[0028] (Mn: 0.05-1.0%) Mn (manganese) is an element that enhances the strength of ferritic stainless steel. If the Mn content is less than 0.05%, this effect cannot be obtained. On the other hand, excessive addition of Mn leads to a decrease in cold workability. Therefore, the amount of Mn added is set to 0.05 to 1.0%.
[0029] (P:0.001~0.04%) P (phosphorus) is an element that deteriorates the toughness and corrosion resistance of ferritic stainless steel. Therefore, the upper limit of P addition is set at 0.04%. The lower the P content, the better the corrosion resistance, but de-P refining stainless steel is thermodynamically extremely difficult because Cr reduces the P activity. Therefore, the lower limit of P addition is set at 0.001%.
[0030] (S:0.001~0.01%) S (sulfur) is an ingredient that generates oxysulfides (acids and sulfides) together with La and oxygen (O), which can cause the crystal alignment with primary ferrite to be significantly lost. For this reason, the upper limit of the amount of S added is set at 0.01%. On the other hand, the lower limit of the amount of S added is a concentration that can be achieved by strengthening the desulfurization refining, but it is uneconomical because it places a large burden on refractories and other materials during refining. For this reason, the lower limit of the amount of S added is set at 0.001%.
[0031] (Cr: 10.5~31.0%) Cr (chromium) is an essential element for ensuring corrosion resistance and heat resistance, and if the amount of Cr added is less than 10.5%, sufficient corrosion resistance and heat resistance cannot be obtained, while if the amount of Cr added exceeds 31.0%, it leads to a decrease in cold workability and toughness, so the amount of Cr added is limited to the range of 10.5 to 31.0%. When particularly high corrosion resistance and workability are required, it is preferable to set the amount of Cr added to 11 to 25%.
[0032] (Al: 0.006~0.20%) Al (aluminum) is an effective element as a deoxidizer, similar to Si. It is also necessary for desulfurization to improve corrosion resistance. If the amount of Al added is less than 0.006%, excess oxygen remains, and Ce forms a complex oxide with Mn and Cr oxides as in the case of Si being less than 0.2%, and does not function as a nucleation site. On the other hand, if the amount of Al added exceeds 0.20%, a complex oxide of Al and Ce may be formed. In this case, it also does not function as a nucleation site. Therefore, the amount of Al added is set to the range of 0.006 to 0.20%. It was recognized that if Al is 0.005% or less, a complex oxide is formed with Ce oxide-based inclusions, but this complex oxide does not become a solidification nucleation site, and the solidification structure does not become fine. However, since the range in which complex oxides are not formed has been clarified, 0.006% or more is added in order to contribute to the ferritic stainless steel sheet by the desulfurization and denitrification effects.
[0033] (Nb: 0.03-0.8%, Ti: 0.01-0.2%) In ferritic stainless steel sheets, Nb (niobium) and Ti (titanium) are elements that precipitate and fix C and N, which are harmful to press formability, and effectively contribute to softening and improving workability. When surface defects in steel sheets are a priority, Ti is not added because the resulting TiN causes surface defects. Therefore, Ti is selectively added depending on the required properties of the steel sheet. If Nb is added in excess of 0.8%, or Ti is added in excess of 0.2%, the effect of these components reaches saturation. Therefore, the upper limit of Nb addition is set at 0.8%, and the upper limit of Ti addition at 0.2%. The lower limit of Nb addition is set at 0.03%, and the lower limit of Ti addition at 0.01%, which are the minimum concentrations required as a C and N stabilizer to prevent the reaction of Cr with C and N in the steel to produce Cr carbo-nitrides.
[0034] (Ce: 0.01~0.35%) If the amount of Ce (cerium) is less than 0.01%, it will react with oxygen and Si and Al present in the molten steel to form complex oxides that do not serve as solidification nucleation sites. Therefore, the lower limit of the Ce content is 0.01%. If the amount of Ce added exceeds 0.35%, it will react with oxygen in the slag or refractories during refining because Ce has a very strong oxygen affinity, and Ce oxide clusters may be formed. Since clusters are likely to cause surface defects on cold-rolled steel sheets, the upper limit of the Ce content is set at 0.35%.
[0035] (Total oxygen amount (TO): 0.001~0.01%) Total oxygen (TO) is an important element for generating Ce oxide-based inclusions that act as solidification nucleation sites, and it is essential that the relationship with the Ce concentration satisfies formula (1). If the TO concentration is less than 0.001%, the number of Ce oxide-based inclusions required for nucleation sites cannot be obtained. If it exceeds 0.01%, the number of Ce oxide-based inclusions becomes too large, which leads to clustering. Clusters of Ce oxide-based inclusions cause surface defects on cold-rolled steel sheets. The "total oxygen content (TO)" refers to the total content of oxygen in the steel sheet and oxygen present as inclusions such as oxides and sulfates.
[0036] Furthermore, the stainless steel sheet of the present invention may further contain the optional additive components described below. (Cu: 0.01% to 2.0%) Copper (Cu) is an element that contributes to improving corrosion resistance. It is desirable to add Cu in the range of 0.01 to 2.0%.
[0037] (Mo: 0.01% to 3.0%) Mo (molybdenum) is an element that further improves corrosion resistance, and it is desirable to add it in the range of 0.01 to 3.0%.
[0038] (W:0.002~3.0%) W (tungsten) is also an element that further improves high-temperature strength. However, since W is a very expensive element, the preferred range depending on the desired properties is 0.002 to 3.0%.
[0039] (Rare earth metals other than Ce) REM (Rare-Earth Metal) refers to metals such as Sc (Scandium), Y, and lanthanoid series such as Ce, La, Pr (Praseodymium), and Nd (Neodymium), but here it refers to rare earth metals other than Ce, La, and Y. REM has a high affinity with S and acts as an S fixing element, and is expected to have an effect of suppressing CaS formation, so it may be contained in an amount of 0.0005% or more. However, excessive REM content can cause nozzle clogging during casting, and the formation of coarse sulfides can actually lead to a deterioration of corrosion resistance. Therefore, the upper limit of the total amount of REM added is set to 0.0100%.
[0040] (La: 0.001 to 0.1%) When Ce is added, it is often done with an alloy called misch metal, which is a mixture of Ce and La (lanthanum). Misch metal is an alloy containing about 70% Ce and about 30% La. When misch metal is added to molten steel, the upper limit of the amount of Ce that can be added is 0.35%, so the upper limit of the amount of La that can be added is set to 0.1%. Also, when misch metal is added to molten steel, although it depends on the yield of this alloy, the lower limit of the amount of La that can be added is set to 0.001%, because about 0.001% is usually mixed into the molten steel.
[0041] (Y: 0.001~0.008%) Y (yttrium) is an unnecessary element from the viewpoint of improving ridging. However, Y is an element that contributes to improving high-temperature strength. Therefore, Y may be added depending on the required properties of the steel sheet. However, if the amount of Y added is in the range of 0.001 to 0.008%, it has almost no effect on the formation of Ce oxide-based inclusions that act as solidification nuclei. Therefore, the amount of Y added is preferably in the range of 0.001 to 0.008%.
[0042] In addition to the above components, the balance includes Fe and unavoidable impurities. Examples of unavoidable impurities include Zr (zirconium), V (vanadium), B (boron), Ca (calcium), Mg (magnesium), Sn (tin), Ni (nickel), Co (cobalt), Zn (zinc), and Ta (tantalum), which may be unavoidably contained at 0.5% or less. These elements are mixed in from various raw materials used when producing this steel on-site, and if the concentration exceeds the above concentration, they often cause surface defects during hot rolling and surface flaws in the steel sheet. Therefore, during production, it is necessary to pay attention to the content of these elements in the raw materials used. If each of them is 0.5% or less, it does not affect the ridging resistance of the ferritic stainless steel sheet and is acceptable as long as it is an amount that does not hinder the effects of the present invention. EXAMPLES
[0043] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0044] The metal compositions of the ferritic stainless steel sheets in Examples 1 to 8 and Comparative Examples 1 to 8 are shown in Table 1. The ferritic stainless steel sheets in the Examples and Comparative Examples were melted in the actual production line shown below. Slabs were produced by continuous casting, and the occurrence of ridging on the steel sheet surface was checked to determine the surface properties when the steel sheet was made into the final steel sheet.
[0045] Refining was carried out in an electric furnace, converter, and vacuum decarburization equipment (VOD). After that, the ladle containing the molten steel was moved to a tundish, and the molten steel was poured into the tundish from the bottom of the ladle. Next, using a continuous casting device attached to the tundish, the molten steel was poured into a mold through a submerged nozzle so that the target slab would be obtained after solidification and cooling. Furthermore, this slab was subjected to a hot rolling process and a cold rolling process to produce a cold-rolled sheet. In more detail, the steel was melted in the electric furnace, converter, vacuum decarburization equipment (VOD), tundish, and continuous casting process to obtain the composition shown in Table 1. The amount of melting was about 80 tons per charge.
[0046] [Table 1]
[0047] After decarburization and denitrification in a converter and a vacuum decarburizer (VOD), deoxidation refinement was performed using Al or Si in the vacuum decarburizer (VOD). After deoxidation refinement, elements such as Ce, La, Y, Al, and Ti were added to the molten steel in the form of Fe alloy or misch metal (Ce: 75%, La: 25%), changing with each charge. The molten steel was then transported to the tundish, poured into the mold through the tundish, and continuously cast to form a slab with a width of approximately 1050 mm and a thickness of approximately 200 mm. The temperature of the molten steel in the tundish was adjusted to be approximately 50°C higher than the liquidus temperature of the molten steel during continuous casting. Samples were cut out from the obtained slab to investigate the inclusion morphology in the as-solidified state.
[0048] Next, the slab was transported to a hot rolling furnace and inserted into the furnace. The temperature inside the furnace was gradually increased from about 900°C, and after reaching 1200°C, it was heated for about 30 to 45 minutes. After that, it was removed from the furnace and subjected to rough hot rolling and finish hot rolling to obtain a hot rolled coil with a thickness of 4.5 mm. The hot rolled coil was annealed, pickled, and cold rolled, annealed, and pickled to obtain a cold rolled steel sheet with a thickness of 0.8 mm.
[0049] From the obtained cold-rolled steel sheet, a JIS-5 test piece was cut out from the center of the longitudinal direction of the cold-rolled coil parallel to the rolling direction in the same manner as described above. In addition, several plates for inclusion observation were cut out from the area near the cut-out test piece. These plates were stacked and pressed together so that the surface perpendicular to the rolling direction was the observation area, and were used for inclusion observation. If the surface was perpendicular to the rolling direction, it was in a state of being crushed in the up and down rolling directions, and it was judged that the dimension in the width direction of the inclusion was roughly close to the diameter of the inclusion in the solidified state. For this sample, as described above, the inclusion composition and the number of inclusions per unit area and the photographed inclusions were converted to a circle equivalent diameter using MQA (automatic particle analyzer: ASPEX Explore VP: FEI Co., Ltd.). Based on the results, inclusions with a circle equivalent diameter of 5 μm present in the steel sheet were selected and the number per unit area was counted.
[0050] The ridging resistance was evaluated in the same manner as described above, by carrying out a tensile test of JIS No. 5 test piece with an elongation of 15% as specified in JIS Z2214 (tensile test method for metallic materials). The results are shown in Table 2 together with the equiaxed crystal ratio.
[0051] [Table 2]
[0052] In Examples 1 to 8, Ce and TO were within the ranges of the present invention, and as shown in Table 2, the product of Ce (%) and TO (%) in formula (1) was also within the range of the present invention. As a result, the equiaxed crystal ratio of the solidification structure in the ingot was 80% or more in all cases. It was also found that the inclusions with a circle equivalent diameter of 1 to 5 μm observed in the cold-rolled steel sheet were mainly composed of Ce oxides. Furthermore, the number density of these inclusions was 20 pieces / cm in all cases. 2 Based on this equiaxed crystal ratio and number density, in the test of JIS standard JIS Z2214 (Method of tensile test for metal materials), the ridging resistance of 0.8 mm cold-rolled thin sheets was evaluated as A rank or B rank for all ridging heights (μm), which are practically acceptable.
[0053] In Comparative Example 1, the contents of Y and Al are excessive, and Ce is not contained. Since the product of the Ce content (%) and the TO content (%) does not satisfy formula (1), the equiaxed crystal fraction is low at 30%, and Ce oxide-based inclusions are not formed, resulting in a number density of 0. As a result, the evaluation result of ridging resistance is D. Note that Y is not an essential component of the present invention, and although Y oxide is formed as shown in Table 2, the equiaxed crystal fraction was low and the effect on ridging resistance was small. In Comparative Example 2, the Ce content was too low to satisfy formula (1), and therefore the equiaxed crystal fraction was low and the number density of Ce oxide inclusions was low. As a result, the evaluation result for ridging resistance was D. Although Al2O3 was formed in the ingot, the equiaxed crystal fraction was low and the effect on ridging resistance was small.
[0054] In Comparative Example 3, the Ce content is excessive and the Al content is insufficient. The product of the Ce content (%) and the TO content (%) satisfies formula (1), but the equiaxed crystal ratio is low at 45%, and the number density of Ce oxide-based inclusions is 108 pieces / cm 2 However, the evaluation result for ridging resistance was C. Therefore, it is clear that in order to satisfy ridging resistance, it is necessary to satisfy both formula (1) and the number density of Ce oxide-based inclusions. Comparative Example 4 did not contain Ce and added Y, but did not satisfy formula (1) because it did not contain Ce even though the TO content was excessive, and therefore the equiaxed crystal ratio was as low as 10%, and no Ce oxide-based inclusions were formed, resulting in a number density of 0. As a result, the evaluation result for ridging resistance was D.
[0055] In Comparative Example 5, La was added as a rare earth metal instead of Ce, but since it did not contain Ce, formula (1) was not satisfied, and therefore the equiaxed crystal ratio was low at 25%, and Ce oxide-based inclusions were not formed, resulting in a number density of 0. As a result, the evaluation result for ridging resistance was D. In Comparative Example 6, the Y and S contents were excessive, and Y sulfide was formed. Also, The product of Ce content (%) and TO content (%) The formula is (1) I am satisfied but The equiaxed crystal ratio was low at 10%, and the number density of Ce oxide inclusions was only 5, so the evaluation result for ridging resistance was D.
[0056] In Comparative Example 7, La was added as a rare earth metal instead of Ce, but since it did not contain Ce, formula (1) was not satisfied, and therefore the equiaxed crystal ratio was low at 30%, and no Ce oxide-based inclusions were formed, resulting in a number density of 0. As a result, the evaluation result for ridging resistance was D. In Comparative Example 8, the Al content was too low, and excessive S was included, forming Ce sulfide, so that the product of the Ce content (%) and the TO content (%) satisfied formula (1). However, the equiaxed crystal ratio was low at 40%, and the number density of inclusions was 20 pieces / cm 2 In the following, the evaluation result of ridging resistance is given a D. This oxysulfide is a form in which sulfide is generated around an oxide, and it is presumed that the crystal structure is different from that of an oxide of simple Ce, resulting in a large degree of crystal mismatch.
[0057] In the invention examples 1 to 8 in Table 2, the range of the present invention is satisfied, and therefore the evaluation results of the ridging resistance were all good, A or B. On the other hand, the comparative examples 1 to 8 were out of the range of the present invention, and therefore the evaluation results of the ridging resistance were C or D, which revealed that the surface waviness was large and unsuitable as a practical steel sheet. In the present invention, it is possible to manufacture ferritic stainless steel hot-rolled / cold-rolled steel sheets or coils with few surface defects. Furthermore, it is possible to suppress the occurrence of steel sheets that could not be shipped due to surface defects, and to greatly improve the yield of the produced steel sheets. Furthermore, since the occurrence of surface defects of products such as steel sheets and coils is suppressed, the process of polishing the surface can be omitted. Due to these effects, the present invention can contribute to cost reduction, yield improvement, and productivity improvement.
Claims
1. In mass percent, C: 0.001-0.03%, Si: 0.2-1.0%, Mn: 0.05-1.0%, P: 0.001-0.04%, S: 0.001-0.01%, Cr: 10.5-31.0%, Al: 0.006-0.20%, Nb: 0.03 to 0.8%, Ti: 0.01-0.2%, N: 0.001-0.03%, Ce: 0.01 to 0.35%, and T. O (total oxygen concentration): 0.001 to 0.01% and the balance being Fe and unavoidable impurities, the product of the Ce content (%) and the T.O content (%) satisfies the inequality relationship of the following formula (1), and the steel has a steel structure in which Ce oxide-based inclusions formed by bonding with the Ce and the oxygen (O) are present, Among the Ce oxide-based inclusions, those having a circle equivalent diameter of 1 to 5 μm are those having a diameter of 1 cm or less in a cross section perpendicular to the rolling direction of the steel sheet. 2 The density of particles is 20 / cm 2 The above-mentioned ferritic stainless steel sheet has excellent ridging resistance. Formula (1): 1.0×10 -5 ≤ (Ce (%)) × ((T.O (%)) ≤ 1.5×10 -3
2. In mass percent, Cu: 0.01-2.0%, Mo: 0.01-3.0%, W: 0.002-3.0%, La: 0.001 to 0.05%, and 2. The ferritic stainless steel sheet having excellent ridging resistance according to claim 1, further comprising one or more components selected from the group consisting of: Y: 0.001 to 0.008%.
Citation Information
Patent Citations
Ferritic stainless steel excellent in workability and corrosion resistance and production of thin steel sheet thereof
JP2000212704A
Ferritic stainless steel excellent in workability and corrosion resistance and production of its thin steel sheet
JP2001011582A
Erritic chromium steel sheet excellent in surface haracteristic and ridging resistance, and its production method
JP2001279388A
Ti-CONTAINING HIGH WORKABILITY FERRITIC CHROMIUM STEEL SHEET HAVING EXCELLENT RIDGING RESISTANCE, AND PRODUCTION METHOD THEREFOR
JP2004169150A
Ferritic chromium steel sheet with excellent surface properties and ridging resistance, and method for producing the same
JP4238454B2